Software Quality: Assessment on the Organizational, Technological and User-related Determinants in the Philippine Setting - Zacarias, Jerhmie James A. (International Journal of Computing Sciences Research; Vol 1 No 2 (2017): Vol 1, No 2, 2017)
Purpose – This mixed method descriptive study aimed to show the impact of Organizational, Technological and User-related factors on software quality. It also assessed the strength of association between these factors and software quality attributes. Method – Toward this goal, data from 405 employees of member companies of the Philippines Software Industry Association (PSIA), together with Emerson Electric Asia and NGA Human Resources were analyzed. Results and Conclusion – The results showed that values of sampling adequacy Kaiser-Meyer-Olkin (KMO) for organizational, technological and user-related determinants are higher than the standard, indicating a good and reliable sample size. The exploratory factors were selected through series of Monte Carlo PCA for parallel analysis on which three components were extracted and retained from each group of determinants that best represented the factors. Organizational determinants of software quality retained “Company Culture”, “Time Resource” and “Process Management”. User-related determinants retained “Level of User Involvement”, “User Resistance to Change” and “Users’ Training on Systems”. Technological determinants retained “Input-Output Services”, “Type of Database Model Used” and “Network Reliability”. Results of logistic regression then showed that organizational, user-related and technological determinants are strongly associated with software quality presented in five attributes: Ease of Use, Maintainability, Relevance, Reliability and Usefulness. Research Implications – This study is by far the first in the Philippines and is very relevant as the country is slowly becoming a global titan in the Business Process Outsource business. The results obtained are beneficial for the academe to devise curricula that would prepare students to the IT industry, and to industry’s senior management to devise software quality improvement programs to align IT strategies to business strategies; thus, having an IT enabled business strategy.